ANALISIS MOLEKULER KERANG (Anadara sp.) MENGGUNAKAN MARKER GEN CYTOCHROME OXYDASE SUBUNIT 1 (CO1) DI PERAIRAN PERCUT SEI TUAN - Dwi Pratiwi, Anggrainy; Idami, Zahratul; Manalu, Kartika (Universitas Cokroaminoto Palopo, 2024)
Anadara sp. clams are very popular clams among the community. Anadara sp. also usually live in waters with muddy and sandy surfaces. DNA barcoding is a barcode sequence to identify unknown species. CO1 is a molecular marker commonly used in molecular research on animals. The purpose of this study was to determine the species of Anadara sp. clams found in Percut Sei Tuan Waters using gene markers, the diversity of Anadara sp. clams using CO1 Gene Markers, and the kinship of Anadara sp. clams found in Percut Sei Tuan Waters. This study has 4 stages, namely DNA isolation using the Favorgen kit, PCR amplification, electrophoresis and sequencing. The DNA sequencing results were analyzed using the MEGA 11 application. The results showed that of the three samples that had been analyzed using the CO1 gene marker obtained using BLAST and NCBI, namely the Anadara granosa, Anadara antiquata, and Anadara gubernaculum samples. With the calculation results of higher AT content (28.9%) and lower GC content (20.12%) which states that the species is more primitive. In the pairwise distance matrix, the samples of Anadara antiquata (Percut Sei Tuan) and Anadara granosa (Percut Sei Tuan) which are in the same clade with different sub clades have a genetic distance ranging from 111.45 to 213.77. The phylogenetic tree also shows that the three samples have a close kinship relationship.